Ensinando a ensinar: efeitos de um programa de ensino de empatia em docentes do 1º ano do ensino fundamental na rede municipal de Sobral – CE - Nobre, Emanuela Cedro Farias (2023)
The National Common Curricular Base presents the essential learning that ensures students develop pedagogical skills, learning and development rights. In this understanding, we identify social skills as part of global development, among these, “empathy”. The present study aimed to investigate the effects of an empathy teaching program on teachers in the 1st year of elementary school in the Municipal Network of Sobral-CE on their empathic skills and their strategies for teaching social skills to students. Two schools participated in the research, selected by the largest number of teachers working in the 1st year. The procedure was divided into three phases: in the 1st phase, an individual form was applied (Falcone et al. Empathy Inventory (2008) and an objective question), to probe empathic behavior and learn about the teaching practices already developed by the participants; the 2nd phase consisted of a workshop, in which only school B participated, so that school A functioned as a comparative group about the intervention; and in the 3rd phase, the effects of the workshop on the empathetic behavioral aspects of the participants, as well as on their teaching strategies, were observed. Data collection occurred through participant observation, records in the field diary and the form. It was not possible to identify consistent changes in learning empathy or learning empathy teaching skills, in the intervention carried out. However, we emphasize the contribution to the discussion on the relevance of the topic in question.